How can sense-data processing generate perception? - Ghattas, Marian Reda Asaad (AUC Knowledge Fountain, 2020)
Sensory perception is an experience that we get on a continuous basis. We live through the experience, we get introduced to things that we consider completely different from ourselves, we get through the event and sometimes recall the features of the entities that we encounter but at other times, we don’t. The study of sensory perception interests diverse disciplines and is a concern of epistemology, or the theory of knowledge. The question of if and how sense perception yields reliable knowledge has been a main subject matter in the study of knowledge throughout the history of philosophy. Different epistemological traditions grappled with this question, empiricism is one school that is positive about this inquiry, it was “expanded by Locke in the seventeenth century” and under David Hume in the eighteenth century. The two famous figures developed arguments to admit of knowledge that is achieved using the senses and to combat a rationalist “commitment to ideas or concepts which are themselves not acquired from sense experience.” Their call for admitting the possibility of empirical knowledge was met with criticism and skepticism. The skeptic views emerged equally from within the empirical tradition as in Hume’s skepticism and from the rationalist tradition. The skeptical puzzles were presented mainly by “René Descartes in the seventeenth century and David Hume in the eighteenth” and continued to influence the epistemological tradition that many philosophers such as “Leibniz, Bayle, Voltaire, and Kant” and later “Mill, Mach, James, Russell, Moore and Wittgenstein” had to “deal with problems which can be traced back to Descartes and Hume.” The Twentieth Century was a time when empiricism re-emerged despite the opposing tides. Some answers were given to address these skeptical worries, appealing to ordinary language was one of these answers, this appeal came from “philosophers as Wittgenstein, Austin and Ryle,” who decided “that the correct approach in epistemology lies in appealing to the ordinary use of the terms of epistemic appraisal.” Other endeavours focused on analysing sense perception. Proponents of this analytic method were philosophers, like Bertrand Russell and A. J. Ayer, who paved the road for the logical positivist school of Vienna. The term “sense-data” was introduced by William James in 1890 and was adopted by “Russell and Moore… retaining a central place in the vocabulary used by philosophers of perception ever since.” Paul Snowdon suggests that sense-data theory had three different models in the twentieth century: (1) what he calls the dominant model, which is a strict model that takes sense-data as real and extra objects involved in our perceptual experience, (2) a weaker model, where G. E. Moore was investigating with great uncertainty the kind of objects which sense-data are, and (3) a model proposed by A. J. Ayer, where sense-data were assigned the function of being just a linguistic use. The interesting thing about these models is that they represent a metaphysical study of sensory perception. The interest has thus shifted from discussing the epistemic justification of sense perception to the metaphysical question of the nature of sense perception. I follow this line in the current thesis, the aim is to understand the process of experiential occurrences that come to the mind during the process of sensory perception. I explore what kind of object comes to the mind of the perceiver within sensory awareness and the nature of that object with which the perceiver gets acquainted. The discussion might be related to its epistemological background, but there will be no consideration of the epistemic aspect of the topic and the latter will be left to the reader’s judgment and for future inspection. The work is a defense of sense-data as real entities, sense-data are real objects without which a lot of sensory phenomena will not be explicable, they are private subjective entities that exhibit the qualities perceived during a sensory experience. In the first chapter, I argue that sense-data are real and that they bear the perceived qualities by presenting the Argument from Hallucination and the Argument from Illusion, I thus refute the naive realist account of perception and its related disjunctivist view that is being used in some naive realist positions to explain the phenomena of hallucination. A disjunctivist view seeks to explain hallucinations without introducing extra entities like sense-data and I refute this position. In the second chapter, I argue that sense-data are the only objects of perception, but that they aren’t the only objects that exist and thus, I differentiate between the concept of perception and the concept of existence and accordingly refute a phenomenalist or idealist account. I rather defend a representative account of perception which differentiates between two sorts of exsisting objects, mind-independent and mind-dependent objects, of whom only one is perceived. In the third chapter, I suggest that a causal relationship holds between these two kinds of object, i.e. the mind-independent and mind-dependent, and I argue that covariance of perceived sense-data of the two suggest this causal link. The aim of this thesis is to defend a representative, but all the same, physicalist account of perception. The account admits that (1) the process of perception involves mind-dependent objects, and (2) that these objects, or sense-data, are different from the mind-independet objects and (3) that they are physical.